VOLUNNTARY COMPLIANCE DENGAN KONSEP KEADILAN PAJAK PERSPEKTIF IBNU KHALDUN BAGI WAJIB PAJAK - Andriani, Sri (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
This research is to identify and analyze the concept of voluntary compliance with the concept of Ibn Khaldun's perspective of tax justice for tax duty. Research with qualitative descriptive type which uses data through interviews with participants: religious leaders, tax officials, tax consultants, tax academics based on the slippery slope framework research results show that voluntary compliance / tax compliance can be defined as mandatory will taxes to be subject to tax regulations in a country. The measurement of compliance that is measured by the knowledge and concept of justice shows that 25 respondents chose strongly agree and 12 respondents chose agree from 37 respondents, meaning that the community realized that tax was the country's biggest source of revenue. Public knowledge about self-assessment shows an average of 3.35, which means that the community has the potential to choose neutral in their knowledge, and 3.3 which shows the level of tax compliance. This tax compliance behavior arises because there is a fairly regulated income tax system, the way income tax is fairly distributed to each taxpayer, and the income tax that is charged is carried out fairly. The principles of convenience and productivity in the realization of taxes which are considered oppressive are emphasized with the concept of equality and neutrality. In other words, someone's awareness is recognized by how much someone's knowledge about the law, that someone's awareness is recognized by how much someone's knowledge about the law.